Marine-Inspired Bis-indoles Possessing Antiproliferative Activity against Breast Cancer; Design, Synthesis, and Biological Evaluation - Wagdy M. Eldehna; Ghada S. Hassan; Sara T. Al-Rashood; Hamad M. Alkahtani; Abdulrahman A. Almehizia; Ghada H. Al-Ansary (Marine Drugs, 2020)
Diverse indoles and bis-indoles extracted from marine sources have been identified as promising anticancer leads. Herein, we designed and synthesized novel bis-indole series 7a–f and 9a–h as Topsentin and Nortopsentin analogs. Our design is based on replacing the heterocyclic spacer in the natural leads by a more flexible hydrazide linker while sparing the two peripheral indole rings. All the synthesized bis-indoles were examined for their antiproliferative action against human breast cancer (MCF-7 and MDA-MB-231) cell lines. The most potent congeners 7e and 9a against MCF-7 cells (IC50 = 0.44 ± 0.01 and 1.28 ± 0.04 μM, respectively) induced apoptosis in MCF-7 cells (23.7-, and 16.8-fold increase in the total apoptosis percentage) as evident by the externalization of plasma membrane phosphatidylserine detected by Annexin V-FITC/PI assay. This evidence was supported by the Bax/Bcl-2 ratio augmentation (18.65- and 11.1-fold compared to control) with a concomitant increase in the level of caspase-3 (11.7- and 9.5-fold) and p53 (15.4- and 11.75-fold). Both compounds arrested the cell cycle mainly in the G2/M phase. Furthermore, 7e and 9a displayed good selectivity toward tumor cells (S.I. = 38.7 and 18.3), upon testing of their cytotoxicity toward non-tumorigenic breast MCF-10A cells. Finally, compounds 7a, 7b, 7d, 7e, and 9a were examined for their plausible CDK2 inhibitory action. The obtained results (% inhibition range: 16%–58%) unveiled incompetence of the target bis-indoles to inhibit CDK2 significantly. Collectively, these results suggested that herein reported bis-indoles are good lead compounds for further optimization and development as potential efficient anti-breast cancer drugs.